Pulmonary Artery Sarcoma Masquerading as Chronic Pulmonary Thromboembolism - (:unkn) unknown (TEXAS HEART INST, 2014)
We describe the case of a 60-year-old woman who presented with pulmonary artery sarcoma, a very rare tumor of the cardiovascular system. Her tumor was initially misdiagnosed as chronic pulmonary thromboembolism, and she underwent pulmonary endarterectomy. Early diagnosis of primary pulmonary artery sarcoma is crucial. That alternative should always be considered before settling on a diagnosis of pulmonary embolism. Suspicion should be aroused by the failure of anticoagulant treatment to alleviate pulmonary perfusion abnormalities and systemic symptoms. Surgical resection of the tumor-preferably by pulmonary endarterectomy, followed by reconstruction as needed-is currently the most promising treatment for pulmonary artery sarcoma.
Keywords: Diagnosis, differential; endarterectomy; fluorodeoxyglucose F18/diagnostic use; hemangiosarcoma/diagnosis/surgery; positron emission tomography; pulmonary artery/pathology/surgery; pulmonary embolism; sarcoma/diagnosis/surgery; tomography, X-ray computed; tunica intima; vascular neoplasms/diagnosis/surgery; DIFFERENTIAL-DIAGNOSIS; EBUS-TBNA; MANAGEMENT